Ten Americans from Pace. - Pace Gallery, New York (London : Wildenstein, 1980)
Close, Chuck ; Pastel, Linda ; Dine, Jim ; Krasner, Lee ; Marden, Brice ; Martin, Agnes ; Nevelson, Louise ; Reinhardt, Ad ; Rothko, Mark ; Samaras, Lucas ; Smith, Tony
Wildenstein presents Ten Americans from Pace, Wildenstein, London, 18th June - 18th July, 1980
boek
Keywords: Amerika